Primary Pancreatic Leiomyosarcoma - Kocakoc, Ercan (Kowsar, 2014)
Primary pancreatic leiomyosarcomas are rare malignant neoplasms with an aggressive course and a large size. A 56-year-old woman presented with an 8-year history of abdominal pain. Multislice computed tomography revealed a large heterogeneous mass with necrotic, calcified and macroscopic fatty areas. The tumor was excised. Histopathological evaluation revealed leiomyosarcoma of the pancreas. If a patient has a large size mass with a cystic-necrotic component, pancreatic leiomyosarcoma should be considered in the differential diagnosis list after excluding other common differential diagnoses.